Profiles of drug substances, excipients and related methodology. Volume forty one - Brittain, H. G. (Profiles of drug substances, excipients, and related methodology ;, 2016)
Volumes in this widely revered series present comprehensive reviews of drug substances and additional materials, with critical review chapters that summarize information related to the characterization of drug substances and excipients. This organizational structure meets the needs of the pharmaceutical community and allows for the development of a timely vehicle for publishing review materials on this topic.